Do olfactory cues mediate interactions between rodents on northern shortgrass prairie? - Stapp, Paul, author; Van Horne, Beatrice, author; NRC Research Press, publisher (Colorado State University. Libraries, 1996)
We counted captures of free-ranging deer mice (Peromyscus maniculatus) in odor-baited traps to determine whether deer mice use olfactory cues to detect and evade grasshopper mice (Onychomys leucogaster), a predator and possible competitor on northern shortgrass prairie. Avoidance was measured using the frequency of captures in traps containing grasshopper mouse odors compared with that in traps containing odors of an innocuous rodent (Reithrodontomys megalotis) and in clean traps. We predicted that deer mice would be most deterred by odors in areas where grasshopper mice were common, and during winter, when alternative prey for grasshopper mice are less abundant. We also expected reproductive females to show greater avoidance because of the vulnerability of litters in burrows. Surprisingly, deer mice showed no evidence of avoidance in any experiments. These results are consistent with trapping records from capture–recapture studies on our site. We assert that the presence of grasshopper mice may affect the surface activity of deer mice, but that deer mice apparently do not use olfactory cues to avoid grasshopper mice. Taken with other studies noting the lack of avoidance of predator odors by deer mice and similar species, our results suggest that the response of rodents to predator odors is more variable than was previously appreciated.
Abstract in English and French.
Keywords: shortgrass prairie; olfactory cues; Fort Collins, Colorado; deer mice; grasshopper mice; western harvest mice